Stereoscopic image sensor with low-cost RGB filters tunned for the visible range - Carmo, João Paulo Pereira (2011)
This paper presents a low-cost technology for fabricating optical filters arrays tuned for the primary colors. The fabrication process presented in this paper is intended for directly printing the optical filters into a transparent flexible substrate (acetate). The target application of these optical filters is for enabling the acquisition of multicolor stereoscopic images with a sensor made in CMOS technology.